Early Arthrocentesis for Temporomandibular Joint Arthralgia: A Superiority Trial - Dion Tik Shun Li; Lai Ying Luo; Kar Yan Li; Yu-Xiong Su; Justin Durham; Yiu Yan Leung (Elsevier, 2024)
ABSTRACT: Objectives: The aim of this superiority trial was to investigate the clinical outcomes of arthrocentesis as an early treatment supported by use of an occlusal splint vs use of an occlusal splint only in the management of temporomandibular joint (TMJ) arthralgia. Methods: Ninety-five adults presenting with TMJ arthralgia were recruited into the study and randomised into 2 groups: Group 1 received arthrocentesis as an early treatment supported by use of an occlusal splint, whereas group 2 received treatment with an occlusal splint only. Seventy-four patients (group 1: n = 37; group 2: n = 37) completed the 1-year follow-up schedule and were included in the final analysis. Reduction of pain intensity measured by a numeric rating scale and increase in mouth opening distance (unassisted maximal, assisted maximal, and pain-free) was seen in both treatment groups. Results: In group 1, pain intensity significantly decreased at 6 weeks and all subsequent time points compared with group 2. In terms of mouth opening distance, a significant improvement was observed in both groups during the course of treatment, but statistical significance was not seen between the 2 treatment groups. Conclusions: Early arthrocentesis supported by use of an occlusal splint is superior to use of an occlusal splint alone in the treatment of TMJ arthralgia. Arthrocentesis with occlusal splint support could be discussed as first-line treatment for arthralgia of the TMJ, which may co-occur with various painful and nonpainful conditions of TMJ disorders.